Evaluation of in situ ammonia removal in an aerated landfill bioreactor - ÇALLI, BARIŞ; MERTOĞLU, BÜLENT (ELSEVIER SCI LTD, 2006)
The composition of nitrifying bacteria in an aerated landfill bioreactor filled with municipal solid waste incineration bottom ashes and shredded incombustible wastes was monitored and analyzed as a function of time during 1 year operation using molecular techniques. Besides, the effects of differing operational conditions on the bioreactor performance and diversity of nitrifiers were evaluated thoroughly. The results confirmed the viability of rapid aerobic bio-stabilization in an aerated landfill bioreactor operated at various ORP levels (-400 to 150 mV). BOD5 decreased faster than TOC and dropped below 10 mg/l after day 120. Subsequently, it remained quite constant until the end of the operational period. This rapid BOD5 degradation in the aerated landfill bioreactor increased the possibility of nitrification by promoting nitrifying bacteria having high oxygen affinities. The nitrification activity in the bioreactor was approved by identification of intensive amounts of Nitrosomonas-like ammonia oxidizers and Nitrospira related nitrite oxidizers with 16S rDNA and amoA based molecular microbiology techniques. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: in situ nitrification; incineration bottom ash; landfill bioreactor; molecular method; 16S RIBOSOMAL-RNA; WATER TREATMENT PLANTS; NITRIFYING BACTERIA; OXIDIZING BACTERIA; CLASS PROTEOBACTERIA; NITROGEN MANAGEMENT; BETA-SUBDIVISION; LEACHATE; POPULATIONS; DIVERSITY